Bullying on Nursing Students - Rais Azka Ghafara; Bayu Fandi Ahmad; Totok Harjanto; Sri Setiyarini (Jurnal Berita Ilmu Keperawatan, 2022)
Bullying on nursing students occurred in more than half of the population. The incidents of bullying left negative impacts on the victims physically, psychologically, and socially. This study identifies the bullying case on nursing care students during academic learning and the roles of the students when bullying occurred. This descriptive quantitative study applied a survey design. This study used Adolescent Peer Relations Instrument (APRI), distributed via Google Form. The respondents were nursing program students that selected convenience sampling. The sample applied some inclusion criteria: the students had to undergo face-to-face learning and online learning. The sampling stage resulted in 207 respondents from three grades. The study analyzed the data with univariate analysis, in the forms of percentages and frequencies. Verbal bullying occurred with a percentage of 31.4%, social bullying with a percentage of 12.16%, and physical bullying with a percentage of 2.32%. The researchers found that 151 respondents, 78.74%, were bullying victims. A percentage of 93.23% of respondents, 193 respondents were women. A percentage of 85.71%, 12 respondents out of 14 respondents, were male. A percentage of 0.96%, 2 respondents, committed the bullying action. A percentage of 45.89%, 95 respondents defended the victims. 100 respondents or 48.45% of participant in this study were outsiders when bullying happened. This study concluded that most students ever experienced bullying cases with the most incidents of verbal bullying. Most students played the role of outsiders during the incidents of bullying